Desafios da organização pedagógica e curricular diferenciada em uma escola do campo do Município da Transamazônica - Pará - MILÉO, Irlanda do Socorro de Oliveira (Universidade Federal do Espírito Santo, 2022)
This article aims to analyze, albeit in an introductory manner, the understanding and attitude of education professionals regarding the importance of developing a differentiated curriculum in the school socio-educational context located in a rural community, in order to meet the identity demands of different collective subjects who live and work in the field. It questions whether it is possible to develop a differentiated curriculum in rural schools in the municipality of Placa / PA; and what strategies are necessary for differentiated educational practices to guide the curricular proposals of these educational institutions. The qualitative study took place in a public school in the municipal education network, with the participation of a teacher who works in the final years of elementary school, the pedagogical coordinator responsible for monitoring the investigated school, and also the direction and coordination Polo School. The results point to the existence of a school curriculum restricted to the adaptations made by the teachers from the official curricular matrices elaborated by the local Municipal Department of Education, without allowing the effective incorporation of themes that favor socio-educational practices that value the traditional knowledge of families peasants and their ways of life, showing a pedagogical organization of rural schools that is out of touch with training demands that respects the socio-cultural identities existing in the countryside.